(untitled) (Texas Journal of Engineering and Technology, 2024)
The territorial integrity and inviolability of the borders of the Republic of Uzbekistan is one of the national interests. In this regard, the measures that ensure the security and territorial integrity of the State have a special place in the system. The achievements of modern science and technology are now tactically reducing the possibility of easily breaking the borders of the state. Therefore, the border troops have the task of equipping the state border with modern high-tech signaling security complexes along the perimeter of the entire territory. In order to improve the quality of state border protection, the task is to introduce a system that combines various sub-systems into a single complex and provides unified management of all technical means included in it. This article compares the advantages and disadvantages of existing technical tools